P0035 Palliative chemotherapy compared with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for patients with colorectal peritoneal carcinomatosis. (July 2015) - Chia, C.S.; Tan, G.H.; Soo, K.C.; Teo, M.C.
Abstract : Background: Cytoreductive surgery (CRS) and hyperthermic intra-peritoneal chemotherapy (HIPEC) prolong survival in selected patients with colorectal peritoneal carcinomatosis. However, this modality of treatment is not standard therapy, and many patients are offered palliative chemotherapy (PC) instead. We hypothesise that PC is suboptimal as complications from the peritoneal disease often disrupts or prevents the PC. We compared overall survival between patients treated with PC and patients undergoing CRS and HIPEC, and we analysed morbidity in those receiving PC. Methods: We performed a retrospective review of a prospectively maintained database at the National Cancer Centre Singapore from January 2008, to December 2013. 34 patients underwent CRS and HIPEC, 21 patients were treated with PC. Secondary outcomes were frequency of disruption of chemotherapy, need for surgery or invasive interventions, and duration of hospitalisation for complications of peritoneal disease. Findings: Median overall survival for patients receiving PC was 1.7 years (95% confidence interval (CI) 0.7–2.1), but that of CRS and HIPEC was not reached. This was in spite of a longer median follow-up time for patients undergoing CRS and HIPEC of 2.2 years (0.2–7.2) compared with 1.1 years (0.0–3.8) with PC. The hazard of death for a patient treated with PC was 5.5 times that of a patient who underwent CRS and HIPEC ( p < 0.05). Of the PC group, 71.4% had chemotherapy disruptions; 60.0% due to complications of peritoneal disease. 14.3% of patients required emergency surgery with stoma creation for intestinal obstruction, and 23.8% of patients required abdominal cope loop and ureteric stent insertion. Median total duration of unforeseen hospitalisation post-CRS and HIPEC was 11 days (0–149), compared with 21 days (0–85) in the PC group. Interpretation: CRS and HIPEC prolonged survival compared with PC in selected patients with CLR peritoneal carcinomatosis. Patients treated with PC have significant morbidity from disease progression, which disrupts planned chemotherapy and results in significantly longer hospitalisation compared with CRS and HIPEC.